LACK OF KINETIC INTERACTION BETWEEN ZOLPIDEM AND DULOXETINE: RESULTS FROM A DRUG-DRUG INTERACTION STUDY IN HEALTHY VOLUNTEERS - GHELDIU, Ana-Maria; MUNTEAN, Dana Maria; NEAG, Maria Adriana; POPA, Adina; BRICIU, Corina; VLASE, Laurian (Studia Universitatis Babeș-Bolyai Chemia, 2019)
This open-label, non-randomized, two-period and sequential study aimed to evaluate a potential kinetic interaction between zolpidem ((N,N-dimethyl-2-[6-methyl-2-(4-methylphenyl)imidazo[1,2-a]pyridin-3-yl]acetamide), a widely known and used sedative-hypnotic and duloxetine ((3S)-N-methyl-3-naphthalen-1-yloxy-3-thiophen-2-ylpropan-1-amine), an antidepressant. A total of 23 healthy volunteers received the following medications: period 1 (Reference) - zolpidem 5 mg (single dose) and period 2 (Test) - zolpidem 5 mg and duloxetine 30 mg. Non-compartmental method was employed to determine the pharmacokinetic parameters of zolpidem and its main metabolite, zolpidem phenyl-4-carboxylic acid (Z4CA) while analysis of variance (ANOVA) was used to test the differences between study periods. Zolpidem exhibited similar pharmacokinetics with or without duloxetine (Cmax: 59.64±27.64 ng/mL vs 53.28±22.77 ng/mL, AUC0-t: 239.45±158.26 ng*h/mL vs 217.21±135.95 ng*h/mL, AUC0-∞: 245.87±161.84 ng*h/mL vs 224.61±138.86 ng*h/mL, t1/2: 2.97±2.06 vs 3.12±1.86 h). Subsequently, no marked changes were observed for Z4CA. The statistical test confirmed that duloxetine had no significant influence on the exposure to zolpidem and Z4CA (p<0.05 for all pharmacokinetic parameters). In conclusion, the study results excluded the possibility of a pharmacokinetic drug-drug interaction between these two drugs. Future investigations should focus on potential undesirable pharmacodynamic effects.